MOF‐Nanocomposite Mixed‐Matrix Membrane for Dual‐Luminescence Ratiometric Temperature Sensing. Issue 19 (3rd July 2021) - Ding, Yanyun; Lu, Yantong; Yu, Kuangli; Wang, Shuo; Zhao, Dian; Chen, Banglin
Abstract: Accurate measurement of temperature is crucial in many branches of medicine, science, and engineering, and often requires temperature sensors that are noninvasive, of high accuracy, and can spatially resolve thermal fluctuations at the nanoscale. Here a new type of flexible and tailorable mixed‐matrix membranes (MMMs) is introduced, which feature dual‐emitting metal–organic framework (MOF)‐based nanocomposites embedded in polymer matrix, and its potential use in luminescence temperature sensing is evaluated. The as‐prepared "Cdots&RB@ZIF‐8 2 ‐MMM" inherits the luminescence properties of the incorporated Cdots&RB@zeolitic‐imidazolate‐framework (ZIF)‐8 2 nanocomposite and possesses the luminescence of both the blue‐emitting carbon dots (Cdots) and the green‐emitting rhodamine B (RB). Since the fluorescence resonance energy transfer between the two guest emitters is thermally correlated, the thermometric parameter ( I C / I RB ) of the Cdots&RB@ZIF‐8 2 ‐MMM has excellent linear response in the physiological temperature range, with favorable relative sensitivity, spectral repeatability, and structural stability. The new ratiometric membranous thermometers proposed here should initiate further interest in luminescent MOF/polymer hybrids and their diverse sensing applications. Abstract : A flexible and tailorable mixed‐matrix membrane (MMM) featuring dual‐emitting metal–organic framework (MOF)‐based nanocomposites embedded in polymers is reported for a self‐calibrating luminescent temperature sensor. The energy transfer between carbon dots (Cdots) and rhodamine B (RB) molecules makes the Cdots&RB@ZIF‐8 2 ‐MMM responsive to all physiological temperatures with good sensing performance. This study provides a feasible strategy for developing novel ratiometric membranous thermometers.